Inequitable distribution of risks associated with occupational heat exposure driven by trade - Meng Li; Bo Meng; Yong Geng; Fan Tong; Yuning Gao; Norihiko Yamano; Sunghun Lim; Joaquim Guilhoto; Kimiko Uno; Xiaohong Chen (Nature Communications)
Abstract The exposure to extreme heat at workplaces poses substantial threat to human effort and manual labour. This becomes more prominent due to the global dispersion of labour-intensive production activities via trade. We combine a climate model with an input–output model to quantify the risks associated with trade-related occupational extreme heat exposure. Here we show an 89% surge in trade-related labour exposure to extreme heat, escalating from 221.5 to 419.0 billion person-hours between 1995 and 2020. Lower-middle-income and low-income economies constituted 53.7% and 18.3% of global exposure but only 5.7% and 1.0% of global labour compensation. In countries highly susceptible to extreme heat conditions, workers perform tasks in heated conditions for up to about 50% of their working hours. The disproportionate trade effects in redistributing global benefits and costs leads to the inequality in heat exposure between developed and developing economies. In striving for equitable and safe work conditions, workers vulnerable to heat extremes in developing economies should be protected by climate adaptation infrastructure, given their critical roles in the global production system.